Case Report: A challenging diagnosis of an apocrine sweat gland carcinoma - Ahmad, Adeel; Samat, Sajjaad; Tan, Yaohong; Bumpers, Harvey (Frontiers in Surgery, 2024)
The differential diagnosis for an axillary mass in a patient with a previously treated malignancy is broad and definitive tissue diagnosis is required to guide treatment and surveillance strategies. We present the case of a 76-year-old African American male with a history of prostate cancer who presented with a left axillary mass two years after achieving remission from his prostate malignancy. Due to the diagnostic challenge, this excisional biopsy was reviewed at four different academic centers. Although no universal consensus among these institutions' pathologists, but in the context of clinical presentation and anatomic location, the overall clinical findings are consistent with apocrine sweat gland carcinoma. The mass was treated with complete local surgical excision, though regional lymph node metastasis occurred 2 years later. Multimodal treatment with surgery and radiation was done with removal of regional metastasis and no distant disease was identified. Primary apocrine carcinoma is a rare cutaneous neoplasm with less than 100 reported cases in the literature. A combination of clinical history and presentation, histomorphology, anatomical location, and immunohistochemistry is used to support the diagnosis and ultimately drive management.